PENGARUH KOSENTRASI BIOAKTIVATOR MIKROORGANISME LOKAL (MOL) DARI KEONG MAS (Pomacea canaliculata L.) TERHADAP PRODUKSI CABAI RAWIT (Capsicum frutescens L.) SEBAGAI SUMBER BELAJAR BIOLOGI - Agung Eko Nugroho; Anak Agung Oka; HRA Mulyani (EDUBIOLOCK, 2021)
The aims of this study are 1) knowing the effect of MOL concentration of conch mas on cayenne pepper production and 2) knowing the concentration of MOL from conch mas is most optimal for cayenne pepper production. The study used a complete randomized design (RAL) and data analysis using a single-track ANAVA against cayenne pepper production. The study used 4 treatments (4% concentration, 7%, 10%, and 13%), 1 control, and 5 repeats. The results of the study showed that there is an effect of giving MOL and mol concentration of 7% conch mas is the most optimal for the production of cayenne pepper (Capsicum frustescens L.) with a yield of 2.5 kg of 1181 pieces higher than the three concentrate treatments tested. MOL consisting of a mixture of conch mas containing macronutrient protein 12.2 mg, Phosfor (P) 60 mg, potassium (K) 17 mg, as well as various other nutrients such as C, Mn, Cu, and Zn greatly affect the number of fruits/trees.